STUDENT PERCEPTION OF THE ROLE OF LECTURERS AS MENTORS IN SELF-DEVELOPMENT - Maghfirah, Ridha; Nurhayati Selian, Sri (International Journal of Multidisciplinary Reseach, 2025)
Student self-development encompasses cognitive, emotional, social, and professional development, essential for facing academic and social challenges. Lecturers play a central role as mentors in this process. However, mentoring in higher education is often suboptimal and informal. This study aims to understand students’ perceptions of the role of lecturers as mentors in self-development. The research method used was descriptive qualitative, using in-depth interviews with three students at the University of Muhammadiyah Aceh who had participated in lecturer mentoring activities. The results showed that students viewed lecturer mentors as guiding figures who provided both academic and emotional support. Lecturers were seen as participating in increasing students’ self-confidence, learning motivation, and critical thinking skills. However, lecturer involvement in mentoring remains variable and not formally structured. Therefore, a more focused mentoring system is needed to strengthen the relationship between lecturers and students so that they can support holistic student self-development.